Antecedents and consequences of destination brand love - A case study from Finnish Lapland - Kaisa Aro; Kati Suomi; Saila Saraniemi (Elsevier, 2022)
Brand love is a relatively new concept in academic discussion that demonstrates consumers’ deepening relationships with brands. The purpose of this study is to conceptualize the antecedents and consequences of destination brand love. This qualitative case study focuses on the destination brand of Ylläs, which is a large outdoor resort located north of the Arctic Circle in Finnish Lapland. This study builds on the academic literature on brand love, destination brands, and emotional place bonds. The main contribution of the study is the presentation of a framework of antecedents and consequences of destination brand love. The framework provides new knowledge for academics and practitioners alike in conceptualizing tourist-dependent, brand-dependent, and brand-experience-related antecedents and the emotional and behavioral consequences of destination brand love. Our results demonstrate the importance of understanding the extreme emotions related to destinations and encourage further research this rarely studied area.